Practical React Native Build Two Full Projects and One Full Game using React Native - Zammetti, Frank (Apress, 2018)
Discover how to use React Native in the real world, from scratch. This book shows you what React Native has to offer, where it came from, and where it's going. You'll begin with a solid foundation of practical knowledge, and then build on it immediately by constructing three different apps. You'll learn how to use each feature of React Native by working on two full projects and one full game. These aren't just simple React Native Hello World examples (although you'll naturally start there!) but are apps that you can, if you so choose, install on your mobile devices and use for real. Throughout this book, you'll gain real-world familiarity with React Native as well as supporting components from Expo, NativeBase, React Navigation and the Redux and Lodash libraries. You'll also build server-side code for a mobile React Native app to talk to using the popular Node.js and Socket.io library, providing you a holistic view of things even beyond React Native. And, you'll see many helpful tips, tricks and gotchas to watch out for along the way! Practical React Native offers practical exercises that will give you a solid grasp of building apps with React Native, allowing you to springboard into creating more advanced apps on your own.Creating a game with React Native will allow you to see a whole other perspective on what React Native can do.